Thor. 1, The devourer king - Cates, Donny (Marvel Worldwide, Inc., 2020)
"The prince is now a king. All Asgard lies before Thor, the God of Thunder. And after many months of war, the Ten Realms are finally at peace. But the skies above the Realm Eternal are never clear for long. The Black Winter is coming. And the God of the Storm will be powerless before it. Before him lies the Black Winter; behind, a trail of death wrought by his own hand. The God of Thunder hurtles through the cosmos, searching for the power to save Asgard and all existence. But no power in the heavens can save a god - a king - from his bloody duty."--Provided by publisher.